2013
DOI: 10.1088/2040-8978/15/10/105706
|View full text |Cite
|
Sign up to set email alerts
|

Propagation of orbital angular momentum carrying beams through a perturbing medium

Abstract: The orbital angular momentum of light has been suggested as a means of information transfer over free-space, yet the detected optical vortex is known to be sensitive to perturbation. Such effects have been studied theoretically, in particular through turbulence. Here we demonstrate a simple apparatus to introduce turbulence-like distortions to optical fields propagating over a long path. We create vortex beams and observe their propagation through a heated spinning pipe, known to mimic the two primary atmosphe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 41 publications
0
9
0
Order By: Relevance
“…The beam displayed propagation patterns which included the redistribution of energy, scintillation, wandering and spreading and this has also been proved in [33,37]. However di culties are not only encountered in experimental studies; recent work has shown this to be numerically challenging as well [38,39].…”
Section: Resultsmentioning
confidence: 83%
“…The beam displayed propagation patterns which included the redistribution of energy, scintillation, wandering and spreading and this has also been proved in [33,37]. However di culties are not only encountered in experimental studies; recent work has shown this to be numerically challenging as well [38,39].…”
Section: Resultsmentioning
confidence: 83%
“…Of course, links may also be physically tested in a laboratory environment using rotating heated pipes [41], computer-generated holograms loaded on spatial light modulators [42], glass plates [43] and controllable climate chambers [33], [44].…”
Section: Atmospheric Turbulencementioning
confidence: 99%
“…Additional deployment challenges of OAM communication over turbulent channels were discussed [201]- [203]. In laboratories, atmospheric turbulence conditions have been simulated in laboratories, using SLMs [206], heated pipes [207], static diffractive plates [208] and rotating phase plates [209], in order to analyze its effects on OAM carrying beams. The most common model for the aforementioned laboratoryemulated turbulence is the Kolmogorov model.…”
Section: A Free Space Propagation Effectsmentioning
confidence: 99%